Älvängen; constructing socially sustainable place identity through urban form - Yang, Wenqing (My University, 2024)
Cities are attractive to people seeking diverse opportunities and benefits. However, the high cost of living, limited space, disconnection from nature, and the presence of noise and light pollutants often deter individuals from settling in urban areas. In response to these challenges, commuter towns, strategically positioned between urban and rural spaces, have emerged as a promising solution. This development is facilitated by efficient and affordable modern transportation, such as cars and trains. Despite the convenience offered to residents and their role in supporting the growth of major cities, commuter towns often grapple with issues such as uniform layouts, a lack of communal interaction, and difficulty defining their identity between urban and rural spheres. Unlike urban and rural areas, the subject of identity in commuter towns has received insufficient attention. This research endeavors to establish and enhance the place identity of commuter towns by designing urban forms that foster socially sustainable development. The study aims to identify the spatial elements crucial to identitybuilding, emphasizing their consideration during the design process. Älvängen, a small town near Göteborg connected by both a commuting train trail and the E45 motorway, serves as a case study due to its typicality and representativeness. Site visits and analyses reveal that the centre of Älvängen, where daily activities occur most frequently, lacks opportunities for meaningful interactions despite ample unused space. The functionalistic form lacks local features, and the town’s history and built heritage are often overlooked. Integrating the concepts of ”place identity” and ”urban form,” the design proposal seeks to reorganize the urban layout to showcase local features and heritage. In the case of Älvängen, this involves highlighting hidden local features, creating a unique sense of identity for both residents and passersby. Such an approach could make a vital contribution to the sustainable development of the town.
Keywords: place identity, urban form, social sustainability, commuter town